PENGARUH SERVICE QUALITY DAN CUSTOMER EXPERIENCE TERHADAP CUSTOMER LOYALTY (STUDI PADA PENUMPANG FIRST CLASS DOUBLE DECKER BUS ROSALIA INDAH) - Adiy Al Ansori; Anik Lestari Andjarwati (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
Seeing the phenomenon of the last few years, several Otobus Companies in Indonesia are now providing premium class bus services. This method is taken to face competition with other modes of transportation, both trains and planes. This study aims to analyse the influence of service quality and customer experience on First Class Double Decker customer loyalty. This study used a sample of 200 respondents who had travelled by First Class Double Decker Rosalia Indah bus with an age range of 16 to 55 years. The sampling method is judgmental sampling with a Likert scale as a measuring tool. The analysis in this study uses multiple linear regression analysis techniques. The results of this study indicate that the service quality and customer experience variables have a positive and significant effect on customer loyalty. The research implies that bus service providers must maintain or increase customer loyalty by considering service quality and customer experience.